Some New Results on Hadamard Neutral Fractional Nonlinear Volterra-Fredholm Integro-Differential Equations - Hamoud, Ahmed A.; Khandagale, Amol D.; Shah, Rasool; Ghadle, Kirtiwant P. (Discontinuity, Nonlinearity, and Complexity, 2026)
In this manuscript, we mainly focus on the existence and uniqueness of solutions for the Hadamard fractional neutral nonlinear Volterra-Fredholm integro-differential equation with infinite delay. We employ Krasnoselskii's fixed point theorem, Arzelá-Ascoli theorem and Banach contraction principle to show the existence and uniqueness of solutions of our problem. Lastly, we provide applications for the illustration of the obtained theoretical results.